Introducing the Lateral Femoral Condyle Index as a Risk Factor for Anterior Cruciate Ligament Injury. Issue 10 (August 2019) - Hodel, Sandro; Kabelitz, Method; Tondelli, Timo; Vlachopoulos, Lazaros; Sutter, Reto; Fucentese, Sandro F.
Background: The asymmetry of the medial and lateral knee compartments contributes significantly to femorotibial biomechanics and pivoting, and it is reported to be a relevant risk factor for an anterior cruciate ligament (ACL) injury. Purpose: (1) To assess the role of femoral condyle sphericity as a risk factor for an ACL rupture and rerupture. (2) To compare the new risk factor with existing bony morphological risk factors via magnetic resonance imaging (MRI) and to assess the most predictive risk factor for an ACL rupture. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective case-control study of 60 patients was conducted. Three age- and sex-matched cohorts (each n = 20) were analyzed: ACL reruptures, primary ACL ruptures, and a control group consisting of isolated meniscal tears or patients with anterior knee pain without signs of trochlear dysplasia. The lateral femoral condyle index (LFCI) as a novel MRI measurement was developed to quantify femoral sphericity. In addition, previously known MRI risk factors associated with ACL injury were analyzed (notch width index, medial tibial slope, lateral tibial slope, medial tibial depth, and lateral tibial height). Differences among groups were compared; cutoff values were defined; and diagnostic performance of the risk factors was assessed. The risk factors were subsequently analyzed with multiple logistic regression. Results: The LFCI was significantly smaller in knees with ACL reruptures (median, 0.67; range, 0.59-0.75) and primary ACL ruptures (0.67; range, 0.60-0.75) than in the control group (0.76; range, 0.6-0.81; P < .01). The LFCI yielded the highest area under the curve among the analyzed risk factors: 0.82 (95% CI, 0.7-0.9). A cutoff of 0.70 yielded a sensitivity of 78% and a specificity of 80% to predict an ACL rupture or rerupture (odds ratio, 13.79; 95% CI, 3.67-51.75). In combination with lateral tibial height (cutoff, 3.8 mm) and lateral tibial slope (cutoff, 2.9°), the diagnostic performance was improved. The area under the curve was 0.86 (95% CI, 0.75-0.94), with a sensitivity of 90% and a specificity of 70% (odds ratio, 21.00; 95% CI, 5.10-85.80). Conclusion: A decreased LFCI is associated with an ACL injury. The LFCI, lateral tibial height, and lateral tibial slope are the most predictive risk factors for an ACL injury. These findings might aid clinicians in identifying patients at risk for an ACL injury and inform the patient after reconstruction for a higher risk of rerupture.